Molybdenum doped graphene/TiO2 hybrid photocatalyst for UV/visible photocatalytic applications. (1st March 2018) - Khan, Hayat; Jiang, Zhuoran; Berk, Dimitrios
Graphical abstract: Highlights: Mo-doped TiO2 spherical nanoparticles were uniformly distributed over graphene nanoflakes. A significant red shift is observed in the DRS spectra of Mox -GT powders compared to pure TiO2 . TiO2 was chemically bonded with graphene. e − – h + recombination is reduced via the synergistic effect of Ti 3+ centers, oxygen vacancies, Mo 6+ /Mo 5+ states and graphene. Mox -GT powders exhibited enhanced degradation for methylene blue under UV/visible illumination. Abstract: Graphene/TiO2 photocatalysts are gaining increasing attention for its application in the decomposition of aqueous organic compounds. In this perspective, we have synthesized molybdenum doped graphene/TiO2 (Mox -GT) hybrids via simple sol-gel method. The physico-chemical properties of the samples were characterized by various analytical and spectroscopic techniques. X-ray diffraction studies indicate that pure TiO2 and graphene/TiO2 were composed of anatase with minor brookite phase while Mo doped graphene/TiO2 powders were composed of only anatase phase. Scanning and transmission electron microscopy results showed particles spherical morphology and uniform distribution of particles on graphene nanoflakes. X-ray photoelectron microscopy revealed the presence of surface defects (Ti 3+ centers and oxygen vacancies), dopants electronic states (Mo 6+ /Mo 5+ ), surface hydroxyl groups and the chemical linkage of graphene with TiO2 . UV-diffuse reflectance spectroscopy analysis showed that addition of Mo dopant to graphene/TiO2 greatly extends the absorption band edge to the visible region. In UV and visible light photocatalytic tests Mox -GT composites showed enhanced activities, specifically the Mo0.8 -GT powder outperformed the rest of the prepared photocatalysts in the decomposition of synthetic textile dye, methylene blue. This highest photocatalytic performance is ascribed to the enhanced photo absorption and electron-hole separation, high surface area and pore size and surface defects. Moreover, the obtained encouraging results portrays that the performed work could provide new insights into the fabrication of metal doped graphene/TiO2 nano-hybrid materials as high performance photocatalyst and facilitates their applications in areas such as; environmental remediation's, hydrogen productions, solar and fuel cells.